PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP KEAKTIFAN BELAJAR SISWA KELAS V SDN 100216 - Hainur Insani; Juliani Batubara; Rama nida Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study evaluates the effect of the Make A Match learning model on student learning activity in Social Science lessons (IPAS) in grade V at SDN 100216. The analysis results show that the implementation of this learning model significantly increases student learning activity, with the average activity score in the experimental class reaching 85%, compared to 70% in the control class. These findings indicate that the Make A Match learning model is effective in attracting students' interest and motivation to learn, and can be used as an alternative in the learning process.